Exercise-Induced Excessive Blood Pressure Elevation Is Associated with Cardiac Dysfunction in Male Patients with Essential Hypertension - Binfeng Xia; Pengyu Cao; Li Zhang; Huihui Huang; Rongyu Li; Xia Yin (International Journal of Hypertension)
Objective. Cardiopulmonary exercise testing (CPET) has been used to explore the blood pressure response and potential cardiovascular system structure and dysfunction in male patients with essential hypertension during exercise, to provide a scientific basis for safe and effective exercise rehabilitation and improvement of prognosis. Methods. A total of 100 male patients with essential hypertension (aged 18–60) who were admitted to the outpatient department of the Center for Diagnosis and Treatment of Cardiovascular Diseases of Jilin University from September 2018 to January 2021 were enrolled in this study. The patients had normal cardiac structure in resting state without clinical manifestations of heart failure or systematic regularization of treatment at the time of admission. Symptom-restricted CPET was performed and blood pressure was measured during and after exercise. According to Framingham criteria, male systolic blood pressure (SBP) ≥210 mmHg during exercise was defined as exercise hypertension (EH), and the subjects were divided into EH group (n = 47) and non-EH group (n = 53). Based on whether the oxygen pulse (VO2/HR) plateau appeared immediately after anaerobic threshold (AT), the EH group was further divided into the VO2/HR plateau immediately after AT (EH-ATP) group (n = 19) and EH-non-ATP group (n = 28). The basic clinical data and related parameters, key CPET indicators, were compared between groups. Result. Body mass index (BMI) visceral fat, resting SBP, and SBP variability in EH group were significantly higher than those in non-EH group. Moreover, VO2/HR at AT and the ratio of VO2/HR plateau appearing immediately after AT in EH group were significantly higher than those in the non-EH group. The resting SBP, 15-minute SBP variability, and the presence of VO2/HR plateau were independent risk factors for EH. In addition, work rate (WR) at AT but also WR, oxygen consumption per minute (VO2), VO2/kg, and VO2/HR at peak were significantly lower in the EH-ATP group compared to the EH-non-ATP group. Peak diastolic blood pressure (DBP) increment and decreased △VO2/△WR for AT to peak were independent risk factors for VO2/HR plateau appearing immediately after AT in EH patients. Conclusion. EH patients have impaired autonomic nervous function and are prone to exercise-induced cardiac dysfunction. EH patients with exercise-induced cardiac dysfunction have reduced peak cardiac output and exercise tolerance and impaired vascular diastolic function. CPET examination should be performed on EH patients and EH patients with exercise-induced cardiac dysfunction to develop precise drug therapy and effective individual exercise prescription, to avoid arteriosclerosis and exercise-induced cardiac damage. The retrospective study protocol was approved by medical ethics committee of the First Hospital of Jilin University (AF-IRB-032-06 No. 2021-015). The study was registered with the Chinese Clinical Trials Register, registration number: ChiCTR2100053140.